Characteristics of dairy cow farms with negative economic results - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Following the research carried out within the ADER 2412 project, entitled Research on the economic efficiency of raising sheep, goats, dairy and beef cattle and buffaloes, quantitative data were collected, analyzing the activity of livestock farms located in different counties in Romania , regarding different characteristics: farm size, level of milk production obtained, yields recorded at the farm level, degree of productivity, level of expenditure and income, break- even point. Based on the centralized data, a series of economic and financial indicators were calculated to determine the feasibility of the livestock farm, depending on the county in which it operates, such as: income rate (with or without access to subsidies) , profit rate, exploitation risk rate, security index. In this paper, the emphasis is on the prototype of farms where negative economic results are recorded, in the sense that the factors that determined their identification are identified, thus outlining a series of recommendations to achieve and increase economic effectiveness and efficiency. at farm level.
Keywords: Q10; Q12; 330; dairy cows; exploitation system; economic indicators; financial indicators; efficiency; effectiveness